2011
DOI: 10.1007/s10919-011-0113-6
|View full text |Cite
|
Sign up to set email alerts
|

Bringing an Ecological Perspective to the Study of Aging and Recognition of Emotional Facial Expressions: Past, Current, and Future Methods

Abstract: Older adults perform worse on traditional tests of emotion recognition accuracy than do young adults. In this paper, we review descriptive research to date on age differences in emotion recognition from facial expressions, as well as the primary theoretical frameworks that have been offered to explain these patterns. We propose that this is an area of inquiry that would benefit from an ecological approach in which contextual elements are more explicitly considered and reflected in experimental methods. Use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
129
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(141 citation statements)
references
References 96 publications
9
129
1
2
Order By: Relevance
“…In the area of emotion recognition and aging, Isaacowitz and Stanley (2011) argued that the results of many studies might lead to erroneous conclusions because tasks fail to include important contextual cues for emotion recognition in older adults' ecologies (e.g., temporal,…”
Section: Non-representative Sampling Might Cause Misleading Resultsmentioning
confidence: 99%
“…In the area of emotion recognition and aging, Isaacowitz and Stanley (2011) argued that the results of many studies might lead to erroneous conclusions because tasks fail to include important contextual cues for emotion recognition in older adults' ecologies (e.g., temporal,…”
Section: Non-representative Sampling Might Cause Misleading Resultsmentioning
confidence: 99%
“…Modalities other than facial expressions are less studied, but there is evidence for age-related decrements in emotion recognition in lexical stimuli (Isaacowitz et al, 2007), body postures (Ruffman, Halberstadt, & Murray, 2009), visual scenes (St. Jacques, Dolcos, & Cabeza, 2008), and in dynamic auditory cues, namely speech prosody (e.g., Lambrecht et al, 2012;Mitchell, 2007;Mitchell, Kingston, & Bouças, 2011) and nonverbal vocalizations (Lima, Alves, Scott, & Castro, 2013). Although typically young adults are compared with individuals aged 60 and over (''extreme age group'' design; Isaacowitz & Stanley, 2011), a few studies using finer gradations in age revealed that decrements may proceed linearly with advancing age, with significant differences already in middle-age (e.g., Isaacowitz et al, 2007;Lambrecht et al, 2012;Mill, Allik, Realo, & Valk, 2009;Paulmann, Pell, & Kotz, 2008).…”
Section: Aging and Emotion Recognitionmentioning
confidence: 99%
“…Including middle-aged participants is a significant difference with respect to previous research. In the aging literature, the middle-years are largely neglected and this contributes to obscure continuous shifts in emotion recognition that may be significant relatively early in the adult life span (Isaacowitz & Stanley, 2011). For instance, Isaacowitz et al (2007) found that the greatest decrements in the recognition of facial expressions and lexical stimuli occurred between younger and middle-aged participants (performance remained relatively stable afterwards).…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Over the intervening years, tremendous developments have taken place in the study of aging, especially regarding emotion-related issues such as changes in aging adults' perception of emotional information. The feature paper by Isaacowitz and Stanley (2011) in the present Special Issue is evidence of these changes and offers theorists and researchers exciting challenges for the study of aging and emotion recognition in the coming years. Commentaries by other scholars echo these challenges and suggest even more ways the study of aging and nonverbal behavior revitalizes attention to basic nonverbal questions and methodological strategies.…”
mentioning
confidence: 78%